Performance of elite seated discus throwers in F30s classes: part II: does feet positioning matter? - Frossard, L.; O'Riordan, A.; Smeathers, J. (Prosthetics and Orthotics International, 2012)
Background: Studies on the relationship between performance and design of the throwing frame have been limited. Part I provided only a description of the whole body positioning. Objectives: The specific objectives were (a) to benchmark feet positioning characteristics (i.e. position, spacing and orientation) and (b) to investigate the relationship between performance and these characteristics for male seated discus throwers in F30s classes. Study Design: Descriptive analysis. Methods: A total of 48 attempts performed by 12 stationary discus throwers in F33 and F34 classes during seated discus throwing event of 2002 International Paralympic Committee Athletics World Championships were analysed in this study. Feet positioning was characterised by tridimensional data of the front and back feet position as well as spacing and orientation corresponding to the distance between and the angle made by both feet, respectively. Results: Only 4 of 30 feet positioning characteristics presented a coefficient correlation superior to 0.5, including the feet spacing on mediolateral and anteroposterior axes in F34 class as well as the back foot position and feet spacing on mediolateral axis in F33 class. Conclusions: This study provided key information for a better understanding of the interaction between throwing technique of elite seated throwers and their throwing frame. Clinical relevance: This study aimed at improving the understanding of the relationship between performance and the design of the throwing frame of seated discus throwers, with a particular emphasis on the importance of feet positioning. This knowledge is particularly important in the current debate around general principles underlying design of throwing frame and classification of athletes with a disability, including those with lower limb amputation.